Photoluminescence-Based Current-Voltage Characterisation Of Individual Subcells In Multi-Junction Devices - Alonso,Alvarez D; Ekins-Daukes,N (IEEE Journal of Photovoltaics, 2016)
We demonstrate a photoluminescence based,contactless method to determine the current-voltagecharacteristics of the individual subcells in a multi-junctionsolar cell. The method relies upon the reciprocity relationbetween the absorption and emission properties on a solarcell. Laser light with a suitable energy is used to excitecarriers selectively in one junction and the internal voltagesare deduced from the intensity of the resultingluminescence. The IV curves obtained this way on 1J, 2Jand 6J devices are compared to those obtained usingelectroluminescence. Good agreement is obtained at highinjection conditions while discrepancies at low injection areattributed to in-plane carrier transport.